PERANCANGAN SISTEM INFORMASI PENJUALAN PRODUK SKINCARE PADA TOKO UNDERPRICE SKINCARE BERBASIS MOBILE - Sidabutar, Dewi Purnama; Jamaluddin, Jamaluddin; Siringoringo, Rimbun (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
In the digital era that continues to grow, the use of information technology is increasingly increasing the efficiency and quality of services in various industries. One sector that has adopted digital transformation is the skin care business. Designing a mobile-based skin care product sales information system that is applied to Underprice Skincare stores. The resulting information system integrates technology components with Underprice Skincare store business processes. Database design includes data storage of skin care products, customer information, sales transaction history, and stock status. The mobile application that was built provides access for store employees to provide better service to customers.